A comparative study of selected aspects of corporate liability of directors under Swiss and South African law - Mueller, Dominique Chantal (School For Advanced Legal Studies, 2024)
Corporate liability of directors is a current issue all over the world due to the financial failures of corporations in the United States and Europe in the past years. The current proceedings in Switzerland against former directors of Swissair, who are accused of having caused the grounding of the airline in October 2001, attracts not only the attention of the Swiss public but also the interest of the neighbouring countries. In this dissertation I will first point out the relevant principles of the Swiss corporate law dealing with liability of directors and then compare the legal situation in Switzerland with the legal situation in South Africa. As the analysis of the whole corporate liability issue would go beyond the scope of this dissertation I will focus on Article 754 of the Swiss Code of Obligations (organ liability) and compare it with the South African grounds of liability of directors for breach of their fiduciary duties and their duty of care and skill.